Chitosan-cartilage extracellular matrix hybrid scaffold induces chondrogenic differentiation to adipose-derived stem cells - I-Chan Lin; Tsung-Jen Wang; Chien-Liang Wu; Dai-Hua Lu; Yi-Ru Chen; Kai-Chiang Yang (Regenerative Therapy, 2020)
Introduction: Adipose-derived stem cells (ASCs) are potential cell sources for cartilage tissue engineering. Chitosan has been shown to enhance the stemness and differentiation capability of ASCs, and the native extracellular matrix (ECM) derived from articular cartilage has been also reported to induce chondrogenic differentiation of ASCs. Here we tested the hypothesis that a porous three-dimensional (3D) hybrid scaffold composed of chitosan and cartilage ECM can provide a better environment to induce ASC chondrogenesis. Methods: Mixed solution composed of chitosan and cartilage ECM was frozen and lyophilized to form a composite construct. The porous 3D scaffolds were further crosslinked by genipin and used for ASC culture. Results: Cultivation of ASCs in the chitosan/cartilage ECM composite 3D scaffolds induced the formation of cell spheroids with profound glycosaminoglycan production after 14 and 28 days culture. Chondrogenesis of ASCs seeded in the 3D scaffolds was also evident by mRNA expressions of cartilage-specific gene COL2A1 and ACAN on day 14. Histology and immunohistochemistry on day 28 also showed abundant cartilage-specific macromolecules, namely collagen type II and proteoglycan, deposited in a surface layer of the composite scaffold with tangential layer, transitional layer, and lacunae-like structures. Otherwise, hypertrophic markers collagen type I and X were concentrated in the area beneath the surface. Conclusion: Our findings demonstrated spatial chondrogenic differentiation of ASCs in the chitosan-cartilage ECM composite scaffolds. This 3D hybrid scaffold exhibits great potentials for ASC-based cartilage tissue engineering.